Diel periodicity of aquatic macroinvertebrate drift in a coastal stream in northern Venezuela. Issue 1 (30th November 2018) - Mendoza, M. Daniela; Montoya, José V.; Perez, Belkys Y.
Abstract: Aquatic macroinvertebrates and organic matter (OM) are transported downstream with the current, in a process that is modulated by different mechanisms in the ecosystem. Macroinvertebrate drift and OM transport are processes involving interactions between organisms and the environment at multiple spatial and temporal scales. The objective of this study was to describe benthic aquatic macroinvertebrate drift in one of the least disturbed streams of northern Venezuela during the dry season. Aquatic macroinvertebrate drift and OM transport were assessed on three different dates, sampling every three hours for each diel cycle using three drift nets. Aquatic macroinvertebrate drift exhibited a clear diel pattern, showing higher drift density values at night than those found during daylight, with significant differences among sampling times (two-way ANOVA, F 7, 48  = 33.51, p  < 0.001) but not among months ( F 2, 48  = 2.012, p  > 0.05) with no interaction between factors ( F 14, 48  = 1.152, p  > 0.05). All sampling dates showed the same trend for diel aquatic macroinvertebrate drift patterns with mean values ranging from 0.19 to 14.81 org.m –3 . Transported OM showed no significant differences for the interaction between factors (sampling time*month) ( F 14, 48  = 0.727, p  > 0.05) or among sampling times (two-way ANOVA, F 7, 48  = 1.25, p  > 0.05) and months ( F 2, 48  = 0.049, p  > 0.05) with values ranging from 79.28 to 207.49 mg.m −3 . The San Miguel stream showed a definite diel trend for aquatic macroinvertebrate drift with a peak at 20:00 h dominated by larval shrimp. Our results indicate that drift samples taken at different times along a diel cycle should be considered in bioassessment studies as an important part of any biodiversity survey. This study contributes to comprehend the importance of the integrity of the freshwater–estuarine–marine corridor for the conservation of aquatic fauna and management in tropical coastal streams. Graphical Abstract: